Characteristics of bone metabolism markers during the healing of osteoporotic versus nonosteoporotic metaphyseal long bone fractures: a matched pair analysis - Harhaus-Wähner, Leila; Hitzler, Mirjam Hannah; Moghaddam-Alvandi, Arash; Takur, Caner; Lehnhardt, Marcus; Grützner, Paul Alfred; Wölfl, Christoph Georg (European journal of trauma and emergency surgery, 2012)
Purpose: The activity and metabolism of fracture healing can be monitored quantitatively by measuring bone turnover markers (BTMs) in serum or urine. However, in osteoporotic bone, the exact metabolism processes during the healing of metaphyseal fractures remain unknown. There is no diagnostic approach which currently allows dynamic insight into the fracture healing processes in order to monitor the progression of healing and to assist in therapeutic decision making.MethodsBetween March 2007 and February 2009, 30 patients over 50 years of age who suffered a metaphyseal fracture were included in our study. The levels of the osteoanabolic marker BAP (bone-specific alkaline phosphatase) and osteocatabolic marker β-CTX [crosslinked C-(CTX)-telopeptide-of-type-I-collagen] were monitored during the fracture healing of osteoporotic and nonosteoporotic fractures for a duration of 8 weeks.ResultsAfter an initial decrease of BAP in the first week, the BAP level steadily increased through the fourth week in both groups. The levels of BAP in the osteoporotic group surpassed the healthy group. β-CTX steadily increased in healthy bone up to the fourth week; in osteoporotic bone, β-CTX first increased and, thereafter, decreased from the first week onwards.ConclusionsIn this work, the first molecular biological aspects of osteoporotic fracture healing have been uncovered, helping to explain the mechanisms of delayed fracture healing in osteoporotic bone. The early decrease of reduced β-CTX as well as elevated BAP during the healing process may be the first aspects within the delayed healing of osteoporotic bone. Further studies are necessary in order to achieve more detailed insight to fracture healing and to ascertain the progression of fracture healing as being essential (criteria) for therapeutic decision making.
Gesehen am 23.10.2018